LitCovid in 2022: an information resource for the COVID-19 literature. Issue Volume 51:Issue D1(2023) (9th November 2022) - Chen, Qingyu; Allot, Alexis; Leaman, Robert; Wei, Chih-Hsuan; Aghaarabi, Elaheh; Guerrerio, John J; Xu, Lilly; Lu, Zhiyong
Abstract: LitCovid (https://www.ncbi.nlm.nih.gov/research/coronavirus/ )—first launched in February 2020—is a first-of-its-kind literature hub for tracking up-to-date published research on COVID-19. The number of articles in LitCovid has increased from 55 000 to ∼300 000 over the past 2.5 years, with a consistent growth rate of ∼10 000 articles per month. In addition to the rapid literature growth, the COVID-19 pandemic has evolved dramatically. For instance, the Omicron variant has now accounted for over 98% of new infections in the United States. In response to the continuing evolution of the COVID-19 pandemic, this article describes significant updates to LitCovid over the last 2 years. First, we introduced the long Covid collection consisting of the articles on COVID-19 survivors experiencing ongoing multisystemic symptoms, including respiratory issues, cardiovascular disease, cognitive impairment, and profound fatigue. Second, we provided new annotations on the latest COVID-19 strains and vaccines mentioned in the literature. Third, we improved several existing features with more accurate machine learning algorithms for annotating topics and classifying articles relevant to COVID-19. LitCovid has been widely used with millions of accesses by users worldwide on various information needs and continues to play a critical role in collecting, curating and standardizing the latest knowledge on the COVID-19 literature.